Analisis Simpang Tiga Bersinyal Ruas Jalan Raya Kletek, Kecamatan Taman, Kabupaten Sidoarjo, Menggunakan Metode MKJI 1997 - Ramadhan, Dennys Rafi; Hartatik, Nurani; Safitri, Dika Ayu (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The increase in the number of vehicles due to population growth, if not accompanied by improvements in road capacity, can lead to traffic problems, particularly at the signalized three-leg intersection on Jalan Raya Kletek, Sidoarjo City. This study aims to analyze the traffic volume using the Indonesian Highway Capacity Manual (MKJI, 1997) method. Data were obtained through field surveys that included traffic volume and the geometric conditions of the intersection. The analysis was conducted to determine the intersection capacity, degree of saturation, queue length, stop rate, and delay. The results show that the highest traffic volume occurred on Tuesday between 17.00–18.00 WIB, with 1,130 pcu/hour from the Mojokerto–Sidoarjo direction, 1,069 pcu/hour from the Sidoarjo–Mojokerto direction, and 454 pcu/hour from Jalan Sawunggaling. These data were used as the basis for calculating the degree of saturation according to the MKJI 1997 guidelines.